Transforming PAS file management through digital technologies - Supiatni, Ni Nyoman; Putra, I Putu Agus Dharma; Mazher, Muhammad Ahmad; Karim, B.M. Sajedul; Shrestha, Binay (YAYASAN MITRA PERSADA NUSANTARA, 2024)
In the current era of globalization, digitization has become a significant advancement, often utilized by companies to streamline administrative processes and reduce reliance on paper-based systems. This research explores the effectiveness of using Google Drive for the monthly accumulation of Passenger Service Charge (PSC) files at PT. API. It aims to assess how digital technology can optimize administrative tasks, particularly the storage and management of PAS files. Additionally, the study outlines the procedural steps involved in the accumulation of these files, offering insights into improving service efficiency. The research is conducted through interviews, observations, and documentation at the airport, using qualitative methods to analyse the collected data. The process involves data reduction, summarization, and drawing conclusions to determine how effectively Google Drive enhances the company's file management system. The expected outcomes will provide PT. API with practical recommendations to optimize its PAS file accumulation process and improve overall service efficiency.